Comparison of different three dimensional-printed resorbable materials: In vitro biocompatibility, In vitro degradation rate, and cell differentiation support. (August 2018) - Raddatz, Lukas; Kirsch, Marline; Geier, Dominik; Schaeske, Jörn; Acreman, Kevin; Gentsch, Rafael; Jones, Scott; Karau, Andreas; Washington, Tommy; Stiesch, Meike; Becker, Thomas; Beutel, Sascha; et al.
Biodegradable materials play a crucial role in both material and medical sciences and are frequently used as a primary commodity for implants generation. Due to their material inherent properties, they are supposed to be entirely resorbed by the patients' body after fulfilling their task as a scaffold. This makes a second intervention (e.g. for implant removal) redundant and significantly enhances a patient's post-operative life quality. At the moment, materials for resorbable and biodegradable implants (e.g. polylactic acid or poly-caprolactone polymers) are still intensively studied. They are able to provide mandatory demands such as mechanical strength and attributes needed for high-quality implants. Implants, however, not only need to be made of adequate material, but must also to be personalized in order to meet the customers' needs. Combining three dimensional-printing and high-resolution imaging technologies a new age of implant production comes into sight. Three dimensional images (e.g. magnetic resonance imaging or computed tomography) of tissue defects can be utilized as digital blueprints for personalized implants. Modern additive manufacturing devices are able to use a variety of materials to fabricate custom parts within short periods of time. The combination of high-quality resorbable materials and personalized three dimensional-printing for the custom application will provide the patients with the best suitable and sustainable implants. In this study, we evaluated and compared four resorbable and three dimensional printable materials for their in vitro biocompatibility, in vitro rate of degradation, cell adherence and behavior on these materials as well as support of osteogenic differentiation of human adipose tissue-derived mesenchymal stem cells. The tests were conducted with model constructs of 1 cm 2 surface area fabricated with fused deposition modeling three dimensional-printing technology.